Reflection of the philosophy of education on the curriculum in South Kurdistan 1968-1990 (history and national education for example) - محمد, م.م. ڕۆشنا فائق محمد; ابراهیم, م.م. سۆران حسین ابراهیم (Sulaimani Journal for Humanities, 2025)
With the establishment of the Iraqi Arab state in 1921, the philosophy of education took on a national character, especially after the arrival of Sati Husseiri in the Ministry of Education. This philosophy has been passed down step by step, regardless of the different communities and religions in Iraq and Kurdistan, After the July 14, 1958 revolution, the philosophy of education did not change much for the Kurdish areas, but this situation did not last long due to the September 1961 revolution, Once again, ethnic differences have emerged in terms of education and programs, After the July 17-30, 1968 revolution, the philosophy of education changed significantly and had a profound impact on teachers, schools and curricula, n order to strengthen the Arab Ba'ath Party, the basis of the curriculum was Arab unity and Arab nationalism, working to create that feeling among Iraqi students in general and showing the Arab nation as the only nation in the world, This was incorporated into the programs as a general and specific goal of the philosophy of education, It had a negative impact on Kurdish students, It is known that education and writing were in Arabic in all Kurdish areas, After the announcement of March 11, 1970, most of the programs were translated into Kurdish, As the beginning of a new hope for the Kurdish people, The eighth political report of the Arab Ba'ath Party soon destroyed the hopes of Kurdish students, After the collapse of the revolution, the situation of education had completely changed, At the same time, they are trying to introduce a unified Arab program across the Gulf statesو after the Iraq-Iran war, his philosophy of education reflected Saddam Hussein's words and actionsو Among the programs, especially history, national education without adaptation to contemporary philosophy.
Keywords: Philosophy; Program; Congress; Education; Socialist